PERTANGGUNGJAWABAN NOTARIS ATAS PENYANGKALAN TANDATANGAN SURAT DIBAWAH TANGAN YANG DISAHKAN DIHADAPANNYA (STUDI PUTUSAN NOMOR: 08/MPWN/PROVINSI SUMATERA UTARA/VI/2015) - HERLINA SINTAULI SIHALOHO (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Budiman Ginting, SH, MHum2.  Notaris Dr. Suprayitno, SH, MKn3.  Notaris Dr. Henry Sinaga, SH, MKn Notary is liable for what he has made according to his duty and authority A Study on the Ruling The case in Ruling No. 08/MPWN/Propensi Sumatera Utara/VI/2015 was started The denial of signatures by some parties because they feel that did not sign them. In consequence is that the Deed can be revoked, the Notary can be sued when he does not want to revoke them with the reasons that he does not know about them and he argues that they are signed by his staffs. When the accusers owe someone else, the latter will be harmed since the former does not want to pay off his debt. The Notary also argues that he was out when signing the Deedwas in process and delegated the authority to his staffs. Regional Supervisory Board has given the right decision in imposing a warning to the Notary asitis stipulated in Article 16, paragraph 1, letter a of Law No. 2/2014 which states,in doing his job, a Notary is required to do it with liability, honesty, accuracy, independence, impartiality, and keeping the interest of the related parties concerning legal act.”Keywords: Liability, Underhanded Deed, Notary